Sports betting of adolescents in Croatia: from favorable environment to psychosocial consequences - Dodig, Dora; Ricijaš, Neven; Kranželić, Valentina; Huić, Aleksandra (2013)
All forms of gambling are prohibited for minors (persons under the age of 18) by Croatian Law on Games of Chance. Current and contemporary research in Croatia confirms that minors have access to different types of games of chance - mostly to sports betting which is a widespread activity especially among the younger population of boys (around 34% of high-school boys regularly bet on sport events). This presentation is a part of the scientific project “Habits and characteristics of adolescent gambling in Croatian urban areas” conducted on a representative sample of high-school students (N=1.952) from 4 major urban centers in Croatia. Since 42.67% of all participants reported betting on sports at least once in their lifetime, results in this presentation are based on a total of 833 adolescents - 77.1% boys and 22.9% girls. Mean age is M=16.73 (SD=1.15). Our aim was to explore how many high-school students report that their parents and friends play games of chance, how often they gamble and do they gamble together. We also explored the intensity of different psychological, social, financial and behavioral consequences that have negative impact on their psychosocial development and are a result of their gambling activities. The Canadian adolescent gambling inventory (Wiebe et. al., 2010) was used to assess the severity of gambling related problems. We also asked adolescents about parents’, siblings’ and peers’ frequency of engaging in gambling activities. Adolescents who bet on sports regularly are more likely to have fathers, siblings and friends that also bet on sports. Furthermore, it is more probable that their parents know about their gambling activities and that sometimes they bet on sports together with their fathers. It is interesting how adolescents, who don’t bet on sports regularly, play lottery games and scratch tickets more often with their parents. More intensive adolescent sports betting is positively correlated with more severe psychological, social and financial consequences, as well as with preoccupation with gambling/betting and impaired control. These results not only confirm the accessibility of sports betting to minors in Croatia, but also show that parents have relatively accepting attitudes about these activities. Therefore, future preventive strategies and interventions should not only include adolescents, but also parents and other important stakeholders in order to sensitize them to possible negative outcomes of gambling on healthy psychosocial development of young people.
ENG